Peran Kerjasama Organisasi Sekolah Dalam Meningkatkan Kualitas Pendidikan Di MTs YLPI Ibaadurrahman - Dede Setiawan; Abdul Fajar; Siti Qomariyah (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
This study aims to analyze the role of school organizational cooperation in improving the quality of education at MTs YLPI Ibaadurrahman. School organizational cooperation has a significant role in creating a quality and competitive educational environment. Through close cooperation between all relevant parties, including school leaders, teachers, students and parents, various initiatives and programs can be implemented effectively. This research uses a qualitative approach by collecting data through interviews, observations, and document analysis related to school organizational cooperation at MTs YLPI Ibaadurrahman. The collected data were analyzed thematically to identify the role and impact of school organizational cooperation on the quality of education. The results showed that school organizational cooperation at MTs YLPI Ibaadurrahman has an important role in improving the quality of education. Through synergistic cooperation, school organizations can carry out various activities, such as curriculum development, teacher training, student coaching, and procurement of adequate educational resources. This cooperation also includes collaboration with parents in supporting home learning and optimizing their role as educational partners. In the context of MTs YLPI Ibaadurrahman, the cooperation of school organizations has had a positive impact on the quality of education. This can be seen from the increase in student academic achievement, increased student participation in extracurricular activities, and increased parental satisfaction with the learning process. In addition, this collaboration also contributes to creating an inclusive, harmonious and supportive school climate. In conclusion, school organizational cooperation has an important role in improving the quality of education at MTs YLPI Ibaadurrahman. With close cooperation between school leaders, teachers, students and parents, various programs and initiatives can be carried out effectively, thus creating a quality and competitive educational environment. It is recommended that this collaboration continue to be improved and implemented on an ongoing basis to optimize the quality of education and produce quality graduates.